Anaerobic treatment of rice winery wastewater in an upflow filter packed with steel slag under different hydraulic loading conditions. (October 2015) - Jo, Yeadam; Kim, Jaai; Hwang, Seokhwan; Lee, Changsoo
Highlights: A UAnF packed with blast-furnace slag achieved effective anaerobic biomethanation of RWW. The UAnF reactor retained stable performance at 10–2.2-day HRTs with 84–92% COD removal. The maximum methane yield of 0.33 L/g CODremoved was achieved at 3.4-day HRT with >85% COD removal. The substrate removal and methane production kinetics of the UAnF were successfully evaluated. Methanosaeta strains likely formed the dominant methanogen group in the filter biofilm. Abstract: Rice-washing drainage (RWD), a strong organic wastewater, was anaerobically treated using an upflow filter filled with blast-furnace slag. The continuous performance of the reactor was examined at varying hydraulic retention times (HRTs). The reactor achieved 91.7% chemical oxygen demand removal (CODr) for a 10-day HRT (0.6 g COD/L d organic loading rate) and maintained fairly stable performance until the HRT was shortened to 2.2 days (CODr > 84%). Further decreases in HRT caused process deterioration (CODr < 50% and pH < 5.5 for a 0.7-day HRT). The methane production rate increased with decreasing HRT to reach the peak level for a 1.3-day HRT, whereas the yield was significantly greater for 3.4-day or longer HRTs. The substrate removal and methane production kinetics were successfully evaluated, and the generated kinetic models produced good performance predictions. The methanogenic activity of the reactor likely relies on the filter biofilm, with Methanosaeta being the main driver.